Case study on teachers’ contribution to children’s participation in Finnish preschool classrooms during structured learning sessions - Salminen, Jenni Elina (Frontline Learning Research, 2013)
The main aim of this study was to identify different teaching practices and explore the types of opportunities that they provide for children’s participation in four different Finnish preschool classrooms for 6-year olds during structured learning sessions. Observational data of four preschool teachers were analyzed according to the principles of qualitative content analysis. Three themes of teachers’ practices were identified, which described the key practices through which teachers influence children’s participation, namely, through discussion and conversations; by referring to shared rules and managing the classroom; and through demonstrating pedagogical sensitivity and understanding towards children’s active participation. Further, each teacher was observed implementing these practices in a unique combination in their classrooms, thus, creating different opportunities for participation. The four teachers showed a constructive, enabling, reserved or restrictive/unbalanced stance towards children’s participation. The results of this study highlight the importance of teachers’ pedagogically sensitive attitude as the key to children’s participation. Given that the advantages of participation to learning and development are well established, the results also point to a need to evaluate the prevailing pedagogy and practices more closely from the perspective of participation.